Ekonomi Politik Bahasa Penyiaran di Jaringan Radio Prambors Rassisonia Indonesia - Bonaventura Satya Bharata; Dina Listiorini (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2012)
This article begin from the research of how the language be used in the broadcast radio industry in Indonesia (especially in the radio network Pramboprs Rassisonia) can not be separated from the logic of capitalism. Operational of capitalism ideology in the media industry generally produce uniformity in the media message, including the language and how to speak. But in the case of Prambors radio network which operating in the region, such as in Yogyakarta and Solo, media managers often have to make compromises to include local languages (vocabulary and dialect) be used in the broadcast process. But in allowing the use of local languages is still intended to be closer to his audience which is nothing but a market of radio Prambors Rassisonia.